The Real State: Inside the Congo’s Traffic Police Agency - Sánchez de la Sierra, Raúl; Titeca, Kristof; Xie, Haoyang (Stan); Lameke, Aimable Amani; Malukisa, Albert Jolino (American Economic Review, 2024)
This paper provides insight into a corruption scheme in Kinshasa’s traffic police agency. First, various data collection branches show that the agency’s revenue is five times that from fines and is derived from a coalition of traffic police officials, their managers, and judicial police officers scheming to extort drivers. Second, the analysis of an experiment suggests that the scheme subverts service. Third, the scheme appears to be a rational response to the context, but its logic is widespread. The findings suggest that coalitions of officials, while being socially costly, can yield large illicit revenue, nuancing the notion of state weakness. (JEL D73, H76, K42, O17)